Molecular phylogeny and dynamic evolution of disease resistance genes in the legume family. (December 2016) - Zheng, Fengya; Wu, Haiyang; Zhang, Rongzhi; Li, Shiming; He, Weiming; Wong, Fuk-Ling; Li, Genying; Zhao, Shancen; Lam, Hon-Ming
Abstract Background Legumes are the second-most important crop family in agriculture for its economic and nutritional values. Disease resistance (R -) genes play an important role in responding to pathogen infections in plants. To further increase the yield of legume crops, we need a comprehensive understanding of the evolution ofR -genes in the legume family. Results In this study, we developed a robust pipeline and identified a total of 4, 217R -genes in the genomes of seven sequenced legume species. A dramatic diversity ofR -genes with structural variances indicated a rapid birth-and-death rate during theR -gene evolution in legumes. The number ofR -genes transiently expanded and then quickly contracted after whole-genome duplications, which meant thatR -genes were sensitive to subsequent diploidization. R proteins with theC oiled-c oil (CC) domain are more conserved than others in legumes. Meanwhile, other types of legume R proteins with only one or two typical domains were subjected to higher rates of loss during evolution. AlthoughR -genes evolved quickly in legumes, they tended to undergo purifying selection instead of positive selection during evolution. In addition, domestication events in some legume species preferentially selected for the genes directly involved in the plant-pathogen interaction pathway while suppressing thoseR -genes with low occurrence rates. Conclusions Our results provide insights into the dynamic evolution ofR -genes in the legume family, which will be valuable for facilitating genetic improvements in the disease resistance of legume cultivars.